FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI WHISTLEBLOWING : STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DKI JAKARTA - Winda Dwi Agustiani; Ahmad Basid Hasibuan (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
This study aims to ascertain the determinants of whistleblowing intention. The respondents in this study are 96 auditors who worked at KAP DKI Jakarta. The method used in this research is quantitative method, while the primary data are collected from questionnaires. Data processing is conducted by performing the data quality testing, the classical assumption testing and the hypothesis testing. The results show a positive correlation between professional commitment and whistleblowing intentions, a possitive yet insignificant correlation between organizational commitment and whistleblowing intention and a negative and insignificant correlation between locus of control and whistleblowing intention.